Creating and Assessing an Information Literacy Component in an Undergraduate Specialized Science Class. Issue 2 (3rd April 2017) - Simonsen, Jenni; Sare, Laura; Bankston, Sarah
ABSTRACT: This study addresses the information literacy needs of undergraduate forensic science students to become lifelong learners throughout their careers. Researchers designed a one-credit hour course combining information literacy instruction with forensic science professional seminars. Two separate cohorts were evaluated. The majority of students (75 percent) showed improvement in information literacy skill levels by the end of the course. Students initially scoring lower than the cohort average on a pretest appeared to gain the greatest benefit. Results suggest that this type of instruction could serve as a baseline for undergraduate science programs seeking to improve how students utilize scientific and legal information.